1992
DOI: 10.1016/s0022-5347(17)37024-6
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Access: 3-Dimensional Anatomical Study

Abstract: In an attempt to determine the best route to puncture and access the kidney collecting system we studied 62, 3-dimensional polyester resin endocasts of the pelvicaliceal system together with the intrarenal vessels. A retrograde pyelogram was obtained, and the arterial and venous trees were injected with red and blue resins, respectively. When the resin was still in the gel state, the kidneys were positioned at 30 to 45 degrees and the collecting system was punctured under radioscopy. Since the resin is not opa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 12 publications
0
54
0
5
Order By: Relevance
“…Inadvertent infundibular puncture in the upper pole may have higher bleeding risk than lower pole. Sampaio et al 16 in another study reported that puncturing the upper pole infundibulum led to an interlobar vessel injury in two thirds of the cases, while only 13% of the patients had an arterial injury when lower pole infundibulum was punctured. Taking into consideration the above, it seems that a PCNL technique which combines the safety of a lower calyceal access without compromising SFRs would be an ideal scenario for the management of staghorn calculi.…”
Section: Cuaj -Original Research Sfoungaristos Et Al: Treating Staghomentioning
confidence: 97%
“…Inadvertent infundibular puncture in the upper pole may have higher bleeding risk than lower pole. Sampaio et al 16 in another study reported that puncturing the upper pole infundibulum led to an interlobar vessel injury in two thirds of the cases, while only 13% of the patients had an arterial injury when lower pole infundibulum was punctured. Taking into consideration the above, it seems that a PCNL technique which combines the safety of a lower calyceal access without compromising SFRs would be an ideal scenario for the management of staghorn calculi.…”
Section: Cuaj -Original Research Sfoungaristos Et Al: Treating Staghomentioning
confidence: 97%
“…tarafından yapılan kadavra çalışmaları ile böbrek toplayıcı sistem anatomisi ve damarsal yapıları çok iyi tanımlanmıştır. Böbreğin kaliksiyel kanlanması ve anatomik özellikler gözönüne alındığında alt kaliks girişlerinin komplikasyon açısından en güvenli yol olduğu belirtilmektedir [18]. Ancak, 2004 yılında Kukreja ve arkadaşları giriş yapılan kaliksin komplikasyon gelişimini etkilemediğini bildirmişlerdir [11].…”
Section: Discussionunclassified
“…Sampaio et al 4 reported injury to an interlobar vessel in two thirds of kidneys on puncturing the upperpole infundibulum, while only 13% of kidneys had an arterial injury when accessed through the lowerpole infundibulum. However, when the puncture was through the centre of the calyceal papilla they detected no arterial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…4 Direct entry into an infundibulum risks injury to one of the interlobar vessels or segmental branches of the renal artery, resulting in significant haemorrhage. 4 Inadvertent puncture of an anterior calyx results in more parenchyma being traversed, increasing the risk of bleeding, and makes it more difficult to access the renal pelvis or other portions of the collecting system. The urologist's selection of the optimum tract based on the intrarenal anatomy and the ability to make secondary tracts as required, 5 permit more effective stone removal.…”
mentioning
confidence: 99%